The Influence of Good Governance Implementation and Organizational Culture on Employee Performance with Community Satisfaction as a Mediating Variable at the District Office of East Siantar Pematangsiantar City - Krista Nainggolan; Hengki Mangiring Parulian Simarmata; Henry D. Pardede (Journal of Management and Business Analytics, 2026)
Optimal public service requires the implementation of good governance principles and a strong organizational culture, as both play an important role in improving employee performance and public satisfaction. This study aims to determine and analyze the influence of implementation good governance and organizational culture on employee performance, with public satisfaction as a mediating variable, at the District Office of Siantar Timur Pematangsiantar City. This research employs a quantitative approach. The population consists of the community members who use services at the District Office of Siantar Timur, Pematangsiantar City, with a total sample of 150 respondents selected using the slovin formula. Data analysis was conducted using path analysis to examine direct and indirect effects, and the sobel test to examine the mediation effect. The result show that the implementation of good governance gas positive and significant effect on employee performance. Furthermore, the implementation of good governance and organization culture has a positive and significant effect on public satisfaction. Public satisfaction can mediate the relationship between the implementation of good governance and organizational culture on employee performance at the district Office of Siantar Timur Pematangsiantar City. Data processing was carried out using SPSS version 25.